التكثيف في الشعر العباسي - م.م. شيماء (Journal of College of Education, 2021)
Through the above-mentioned evidence and opinions on this literary term of art which was not an emergency event or a term recently invented . But its roots stands since ancient times, especially in the unit of independent poetic system , or united poetic unit in the poem, where unit including the densest words and a broader meaning or significance which has been referred to in the midst of this research and the final result that we have reached is that the term condensation can be classified in the equation of a new literary list as follows: